Legal Accountability of Land Deed Officials for Issuing Land Transfer Deeds Using Fraudulent Modus Operandi - Aslan Noor Aslan; Ervan Wiguna; Muhammad Akhmal Avshary; Vina Nurlianda; Gilza Azzahra Lukman; Jodi Jordan Joserando; Afif Fuazi (Research Synergy Foundation, 2025)
The Land Deed Official (PPAT) plays a crucial role in ensuring the validity of land rights transfers by issuing authentic deeds. However, in practice, this authority can be abused through fraudulent modus operandi that employ such deeds as instruments of criminal acts, as illustrated by the land mafia case involving Mbah Tupon. The legal issues that arise include the juridical accountability of PPATs involved in issuing land transfer deeds through fraudulent modus operandi, as well as the effectiveness of supervisory and guidance mechanisms in preventing similar practices. This study aims to analyse the forms of PPAT accountability from the perspectives of civil, criminal, and administrative law, as well as to examine the ideal models of supervision and guidance for preventing land mafia practices. The research method employed is normative juridical with statutory, conceptual, and case study approaches, linking land law norms with the professional ethics of PPATs. The results of the study indicate that PPATs involved in fraudulent modus operandi may be held cumulatively liable under all three legal regimes. However, weaknesses in internal supervision systems and the lack of strict administrative sanctions remain loopholes that allow such violations to occur. Reforming supervision policies, strengthening the role of the PPAT Supervisory Council, and digitising the deed-making process are strategic measures to prevent abuse of authority and provide effective legal protection for landowners.